Biomedical titanium alloy prepared by additive manufacturing: Effect of processing on tribology - Roudnicka, Michaela; Bayer, Frantisek; Michalcova, Alena; Kubasek, Jiri; Alzubi, Enas Ghassan Hamed; Vojtech, Dalibor (Manufacturing Technology Journal, 2020)
In the production of a new generation of customized implants, additive manufacturing (AM) is a hot topic. A titanium-based alloy, Ti6Al4V, is one of the most used materials for such applications with regard to its excellent biocompatibility and high mechanical properties which provide it with the capability to bear physiological loads. However, its resistance to wear is rather poor which might cause undesirable loosening of wear particles or even implant failure. Therefore, enhancing wear resistance is desirable. Thanks to a distinctive principle and rapid cooling, AM is known to be able to enhance mechanical properties. In this paper, we thus discuss tribological properties in direct relation to microstructures resulting from AM. We reveal the finest microstructural details of Ti6Al4V alloy prepared by different techniques of AM and discuss also the effect of heat treatment. Complex characterization including transmission electron microscopy, hardness measurement and ball-on-plate wear tests showed a mild contribution of AM to wear resistance of the Ti6Al4V alloy compared to the conventionally produced alloy.
Keywords: additive manufacturing; Ti6Al4V; TEM; tribology